2019
DOI: 10.1371/journal.pone.0224278
|View full text |Cite
|
Sign up to set email alerts
|

Sex differences in the treatment and outcome of emergency general surgery

Abstract: BackgroundSociodemographic characteristics, such as sex, have been shown to influence health care delivery. Acute care surgery models are effective in decreasing mortality and morbidity after emergency surgeries, but sex-based differences in delivery and outcomes have not been explored. Our objective was to explore sex associated differences in the patient characteristics and clinical outcomes of those admitted to emergency general surgery.MethodsA post-hoc analysis of 512 emergency general surgical patients a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(24 citation statements)
references
References 41 publications
0
24
0
Order By: Relevance
“…Here, we analyse all kinds of surgical procedures together and find that female patients were less likely to die than male patients. There are some papers that show a similar trend [ 32 ], but others found no differences between the sexes with respect to mortality [ 33 ]. Therefore, this issue requires more detailed studies in the future.…”
Section: Discussionmentioning
confidence: 99%
“…Here, we analyse all kinds of surgical procedures together and find that female patients were less likely to die than male patients. There are some papers that show a similar trend [ 32 ], but others found no differences between the sexes with respect to mortality [ 33 ]. Therefore, this issue requires more detailed studies in the future.…”
Section: Discussionmentioning
confidence: 99%
“…Medical education must expand to include a range of healthcare conditions, and beyond the lifespan context to consider not only healthcare conditions, but also issues and challenges that affect women’s health and health care. Considerable research has established wide-spread gendered inequities in access to and quality of care [ 7 – 19 , 23 , 24 ], further exacerbated by social determinants of health such as race, ethnicity, culture, education and employment, and other research shows that women’s healthcare concerns and questions are often dismissed [ 20 22 ]. One way to address these problems is to ensure that future generations of physicians are aware of these issues and understand what can be done at the individual, organizational and system levels to prevent and mitigate such inequities.…”
Section: Discussionmentioning
confidence: 99%
“…Research in Canada between 2003 and 2012 revealed that women were less likely than men to receive ideal care for a range of conditions [ 7 , 8 ]. More recent Canadian research also identified gendered disparities in care delivery and patient outcomes for various health conditions including cardiovascular disease [ 9 – 12 ], HIV management [ 13 , 14 ], hip fracture [ 15 ], chronic obstructive pulmonary disease [ 16 ], mental illness [ 17 , 18 ], and emergency surgery [ 19 ]. Another 1225 Canadian women said that truncated discussion of health issues was a frequent problem [ 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…In surgical settings, sex discrepancies exist in both elective and non‐elective situations, where worse outcomes have been reported in women [17, 45, 46]. Women are more likely than men to be iron deficient pre‐operatively [24] and peri‐operative blood transfusion rates are higher in women [47].…”
Section: Clinical Consequencesmentioning
confidence: 99%